Preparation method and application of lithium iron phosphate

By using dispersant in the preparation process of lithium iron phosphate, the slurry viscosity and the solid content are improved, the problems of low tap density of lithium iron phosphate positive electrode material and high viscosity and low solid content in the production process are solved, and the high efficiency and low energy consumption are achieved, and the performance and output of the battery are improved.

CN119683593APending Publication Date: 2025-03-25HENAN BAILI NEW ENERGY MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411854543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

Smart Images

  • Figure BDA0005192514310000121
    Figure BDA0005192514310000121
  • Figure BDA0005192514310000131
    Figure BDA0005192514310000131
  • Figure BDA0005192514310000141
    Figure BDA0005192514310000141
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to a preparation method and application of lithium iron phosphate. The preparation method of the lithium iron phosphate comprises the following steps: (a) carrying out first grinding, first spray drying, first sintering and crushing on a mixed system containing slurry A and a dispersing agent to obtain a precursor; the slurry A comprises an iron source, a lithium source and an additive; and (b) carrying out second grinding, second spray drying and second sintering on a mixed system containing the precursor, a carbon source and the dispersing agent. The preparation method of the lithium iron phosphate has the advantages of low energy consumption, high yield, easiness in operation and the like, the prepared lithium iron phosphate has relatively high tap density and compaction density, and the slurry is low in viscosity and high in solid content during grinding, so that the yield is increased, the production energy consumption is reduced, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a preparation method of lithium iron phosphate and application thereof. Background Art

[0002] Lithium iron phosphate materials are used more and more in automotive power batteries, large energy storage power stations, and power-assisted vehicles because of their rich resources, environmental friendliness, low cost, safety and reliability, and thus the demand for the output of lithium iron phosphate materials is increasing. However, lithium iron phosphate positive electrode materials also have obvious disadvantages: low lithium ion diffusion rate, low conductivity, and low tap density. At present, people have been committed to solving the problem of low conductivity, but have ignored the low tap density of lithium iron phosphate positive electrode materials. The low tap density leads to low volume specific capacity, so that the battery volume is large, which is not conducive to practical use. In addition, in the production process of lithium iron phosphate materials, the viscosity of the slurry becomes higher and higher during the mixing process, resulting in a low solid content of the slurry, which not only leads to low output in the production process, but also increases production energy consumption and increases production costs. Therefore, the production of high-pressure and high-tap lithium iron phosphate positive electrode materials is a key step at this stage.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing lithium iron phosphate and its application. The method for preparing lithium iron phosphate has the advantages of low energy consumption, high output, easy operation, etc. The prepared lithium iron phosphate has high tap density and compaction density, and the slurry viscosity during grinding is low and the solid content is high.

[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0006] One aspect of the present invention relates to a method for preparing lithium iron phosphate, comprising the following steps:

[0007] (a) subjecting a mixed system containing slurry A and a dispersant to first grinding, first spray drying, first sintering and pulverizing to obtain a precursor;

[0008] The slurry A comprises: an iron source, a lithium source and an additive;

[0009] (b) subjecting the mixed system containing the precursor, the carbon source and the dispersant to second grinding, second spray drying and second sintering.

[0010] The method for preparing lithium iron phosphate has the advantages of low energy consumption, high output, and easy operation. The prepared lithium iron phosphate has high tap density and compaction density, low slurry viscosity during grinding, and high solid content, thereby increasing output, reducing production energy consumption, and reducing production costs.

[0011] Another aspect of the present invention also relates to a positive electrode plate, comprising lithium iron phosphate prepared by the lithium iron phosphate preparation method.

[0012] Another aspect of the present invention also relates to a lithium-ion battery, comprising the positive electrode plate.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] (1) The preparation method of lithium iron phosphate provided by the present invention has the advantages of low energy consumption, high output, and easy operation. The prepared lithium iron phosphate has high tap density and compaction density, good electrochemical performance under low temperature environment, low slurry viscosity during grinding, and high solid content, thereby increasing output, reducing production energy consumption, and reducing production costs.

[0015] (2) In the preparation method of lithium iron phosphate provided by the present invention, a dispersant is added during the preparation process. The dispersant, as a carbon source, can not only decompose to generate organic small molecules in the high temperature process, but also promote the pore formation of lithium iron phosphate, control the grain morphology, inhibit the growth of grains, form particles of uneven sizes, so that the large and small particles form a graded distribution, the particles are uniform and dense, and the tap density is increased to 1.5g / cm 3 The above; the dispersant also has a certain reducing property, which can inhibit Fe to a certain extent in the preparation process of lithium iron phosphate 2+ Oxidized to Fe 3+ .

[0016] (3) The preparation method of lithium iron phosphate provided by the present invention uses a dispersant instead of a traditional carbon source, which can avoid the carbon source from being coated on the surface of the lithium iron phosphate in advance, so that the lithium iron phosphate can form a dense sintered body, obtain a harder finished product, and thus effectively improve the tap density of the lithium iron phosphate.

[0017] (4) In the preparation method of lithium iron phosphate provided by the present invention, the dispersant acts as both a carbon source and a viscosity reducer during the material mixing process, can quickly wet the surface of inorganic particles, improve the dispersibility of the raw materials during the mixing process, reduce the viscosity of the grinding materials, and increase the solid content of the slurry from the original 40% to more than 50%. After the solid content is increased, not only the sand grinding efficiency is improved, but also the spraying efficiency is improved, thereby reducing the overall production energy consumption.

[0018] (5) The preparation method of lithium iron phosphate provided by the present invention is to carry out secondary carbon coating after the first sintering is completed, which can not only effectively improve the conductivity of the material but also reduce the size of the material particles and thus refine the particles to increase their compaction density and tap density, and can also reduce the internal resistance of the material, so that the conductivity of the material is further improved. DETAILED DESCRIPTION

[0019] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0020] One aspect of the present invention relates to a method for preparing lithium iron phosphate, comprising the following steps:

[0021] (a) subjecting a mixed system containing slurry A and a dispersant to first grinding, first spray drying, first sintering and pulverizing to obtain a precursor;

[0022] The slurry A comprises: an iron source, a lithium source and an additive;

[0023] (b) subjecting the mixed system containing the precursor, the carbon source and the dispersant to second grinding, second spray drying and second sintering.

[0024] The method for preparing lithium iron phosphate has the advantages of low energy consumption, high output, and easy operation. The prepared lithium iron phosphate has high tap density and compaction density, good electrochemical performance in a low temperature environment, low slurry viscosity during grinding, and high solid content, thereby increasing output, reducing production energy consumption, and reducing production costs.

[0025] The preparation method of lithium iron phosphate adds a dispersant during the preparation process. The dispersant, as a carbon source, can not only decompose to generate organic small molecules in the high temperature process, but also promote the pore formation of lithium iron phosphate, control the grain morphology, inhibit the growth of grains, form particles of uneven sizes, so that the large and small particles form a graded distribution, the particles are uniform and dense, and the tap density is increased to 1.5g / cm 3 The above; the dispersant also has a certain reducing property, which can inhibit Fe to a certain extent in the preparation process of lithium iron phosphate 2+ Oxidized to Fe 3+ .

[0026] The preparation method of lithium iron phosphate uses a dispersant instead of a traditional carbon source, which can avoid the carbon source from being coated on the surface of the lithium iron phosphate in advance, so that the lithium iron phosphate can form a dense sintered body, obtain a harder finished product, and thus effectively improve the tap density of the lithium iron phosphate.

[0027] In the preparation method of lithium iron phosphate, the dispersant acts as both a carbon source and a viscosity reducer during the material mixing process, can quickly wet the surface of inorganic particles, improve the dispersibility of the raw materials during the mixing process, reduce the viscosity of the grinding materials, and increase the solid content of the slurry from the original 40% to more than 50%. After the solid content is increased, not only the sand grinding efficiency is improved, but also the spraying efficiency is improved, thereby reducing the overall production energy consumption.

[0028] The preparation method of lithium iron phosphate is to perform secondary carbon coating after the first sintering is completed, which can not only effectively improve the conductivity of the material but also reduce the size of the material particles and thus refine the particles to increase their compaction density and tap density, and can also reduce the internal resistance of the material, so that the conductivity of the material is further improved.

[0029] Furthermore, the first grinding time is 40 to 60 minutes, including but not limited to any one of 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes or any range between two of them. Grinding within a certain time can accurately control the particle size of the material within an appropriate range.

[0030] Furthermore, the D of the mixed material 50 When the thickness is 0.4 to 0.5 μm (for example, but not limited to, any point value of 0.4 μm, 0.42 μm, 0.44 μm, 0.46 μm, 0.48 μm or 0.5 μm, or a range value between any two of them), the first grinding and the second grinding are finished.

[0031] Furthermore, at the end of the first grinding, the solid content of the mixed material is 50% to 60%, including but not limited to any point value of 50%, 52%, 54%, 56%, 58% or 60% or a range value between any two of them. A dispersant is added to slurry A to reduce the viscosity of the mixed system and increase the solid content of the slurry after grinding, which is conducive to increasing the output and reducing the production cost.

[0032] Furthermore, at the end of the second grinding, the solid content of the mixed material is 50% to 60%, including but not limited to any point value of 50%, 52%, 54%, 56%, 58% or 60% or a range value between any two of them.

[0033] Furthermore, the air inlet temperature of the first spray drying is 200-280°C, including but not limited to any point value of 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C or a range value between any two of them.

[0034] Furthermore, the outlet air temperature of the first spray drying is 80-110°C, including but not limited to any point value of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C or a range value between any two of them.

[0035] Furthermore, the atomizer frequency of the first spray drying is 40-60 Hz, including but not limited to any point value of 40 Hz, 45 Hz, 50 Hz, 55 Hz or 60 Hz or a range value between any two of them.

[0036] Furthermore, the inlet air temperature of the second spray drying is 200-280°C, including but not limited to any point value of 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C or a range value between any two of them.

[0037] Furthermore, the outlet air temperature of the second spray drying is 80-110°C, including but not limited to any point value of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C or a range value between any two of them.

[0038] Furthermore, the atomizer frequency of the second spray drying is 40-60 Hz, including but not limited to any point value of 40 Hz, 45 Hz, 50 Hz, 55 Hz or 60 Hz or a range value between any two of them.

[0039] Furthermore, the first sintering and the second sintering are performed under inert atmosphere conditions.

[0040] The present invention does not specifically limit the type of inert atmosphere, and any conventional inert atmosphere in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the inert atmosphere includes but is not limited to at least one of nitrogen, argon or helium.

[0041] Further, the first sintering temperature is 600-800°C, including but not limited to any point value of 600°C, 630°C, 650°C, 680°C, 700°C, 730°C, 750°C, 780°C or 800°C or a range value between any two of them.

[0042] Furthermore, the first sintering time is 7 to 11 hours, including but not limited to any one of 7 hours, 8 hours, 9 hours, 10 hours or 11 hours or a range between any two of them.

[0043] Further, the temperature of the second sintering is 350-450°C, including but not limited to any point value of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C or 450°C or a range value between any two of them. Lowering the temperature of the second sintering and performing the second sintering at a lower temperature can effectively reduce the performance degradation of the battery in a low temperature environment. The presence of the carbon layer can reduce the viscosity of the electrolyte and promote the migration of lithium ions, thereby improving the discharge efficiency and capacity of the battery at low temperatures.

[0044] Furthermore, the second sintering time is 1 to 3 hours, including but not limited to any one of 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, or a range between any two of them.

[0045] Furthermore, the gas-powder frequency of the pulverization is 20 to 50 Hz, including but not limited to any point value of 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz or 50 Hz or a range value between any two of them.

[0046] The present invention does not specifically limit the type of iron source, and conventional iron sources in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the iron source includes but is not limited to at least one of ferroferric oxide, ferrous sulfate, ferric oxide, ferrous phosphate, ferrous oxalate or ferrous nitrate.

[0047] The present invention does not specifically limit the type of lithium source, and conventional lithium sources in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the lithium source includes but is not limited to at least one of lithium carbonate, lithium chloride, lithium hydroxide, lithium citrate or lithium nitrate.

[0048] Furthermore, the additive includes but is not limited to: at least one of lithium dihydrogen phosphate, ammonium vanadate, ammonium dihydrogen phosphate, niobium pentoxide or titanium dioxide. The additive has the functions of improving the morphology of the material, improving the electrochemical performance and enhancing the stability of the material.

[0049] Furthermore, the molar ratio of lithium, iron and phosphorus in the slurry A is 1:0.95 to 1:0.95 to 1.05, including but not limited to 1:0.95:1.05, 1:0.96:1.03, 1:0.97:1.00, 1:0.98:0.98 or 1:1:0.95.

[0050] Furthermore, the concentration of the additive is 2500-3500 ppm, including but not limited to any point value of 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, 3100 ppm, 3200 ppm, 3300 ppm, 3400 ppm or 3500 ppm or a range value between any two of them.

[0051] Furthermore, in step (a), the mass of the dispersant is 60% to 80% of the total mass of the iron source and the lithium source, including but not limited to any point value of 60%, 65%, 70%, 75% or 80% or a range value between any two of them. Limiting the amount of the dispersant added in step (a) to a certain range can ensure that a sufficient amount of carbon is coated during the first sintering, improve the electrochemical performance of lithium iron phosphate, and effectively reduce the viscosity of the slurry during grinding.

[0052] Furthermore, in step (b), the mass of the dispersant is 1% to 5% of the mass of the precursor, including but not limited to any one of 1%, 2%, 3%, 4% or 5% or any range between the two. Limiting the amount of the dispersant added in step (b) to a certain range can ensure that the precursor and the carbon source are mixed evenly.

[0053] Furthermore, the dispersant includes, but is not limited to, at least one of polyacrylate, polyacrylamide, sodium lauryl sulfate or fatty acid polyethylene glycol ester.

[0054] The present invention does not specifically limit the type of carbon source, and conventional carbon sources in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the carbon source includes but is not limited to at least one of sucrose, PEG, glucose, cellulose, citric acid, carbon black, polyvinyl alcohol, starch or polyethylene glycol.

[0055] Furthermore, the mass of the carbon source is 2% to 6% of the mass of the precursor, including but not limited to any point value of 2%, 3%, 4%, 5% or 6% or a range value between any two of them.

[0056] Another aspect of the present invention also relates to a positive electrode plate, comprising lithium iron phosphate prepared by the lithium iron phosphate preparation method.

[0057] Another aspect of the present invention also relates to a lithium-ion battery, comprising the positive electrode plate.

[0058] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0059] Example 1

[0060] The method for preparing lithium iron phosphate provided in this embodiment comprises the following steps:

[0061] (1) Weigh 4000 g of iron phosphate, 1000 g of lithium carbonate, 13 g of titanium dioxide, 20 g of lithium dihydrogen phosphate and 5033 g of deionized water, add them to a sand mill and grind them for 20 min to obtain slurry A;

[0062] (2) 3250 g of polyacrylate dispersant was added to slurry A, and sand milling was continued for 60 min. After the sand milling was completed, the slurry was transferred to a fine grinder and finely ground to a D50 of 0.42 μm. The finely ground slurry was spray dried in a spray dryer with an inlet air temperature of 200° C.

[0063] (3) The spray material obtained in step (2) is sintered at 760° C. for 9 h under an inert atmosphere, and then crushed to obtain a precursor after sintering;

[0064] (4) Weigh 3000 g of the precursor, 100 g of sucrose, 60 g of the polyacrylate dispersant and 2000 g of deionized water in step (3) and add them to a premixer for premixing for 50 min; after the mixture is premixed in a fine grinder until the D50 is 0.42 μm, the finely ground slurry is spray dried for a second time in a spray dryer at an inlet air temperature of 200° C.;

[0065] (5) The spray material obtained in step (4) is sintered at 350° C. for 2 h under an inert atmosphere, and then crushed to obtain a finished product of lithium iron phosphate.

[0066] Example 2

[0067] The method for preparing lithium iron phosphate provided in this embodiment comprises the following steps:

[0068] (1) Weighing iron phosphate, lithium carbonate, titanium dioxide, lithium dihydrogen phosphate and deionized water, adding them to a sand mill and coarsely grinding them for 20 minutes to obtain slurry A, wherein the solid content of slurry A is 50%, the molar ratio of lithium element, iron element and phosphorus element in slurry A is 1:0.98:1.00, and the concentration of additives in slurry A is 3000 ppm;

[0069] (2) Adding polyacrylamide dispersant to slurry A, the amount of polyacrylamide added is 70% of the total mass of the iron source and the lithium source, and continuing sand milling for 60 minutes; after completion, transferring to a fine grinder for fine grinding until D50 is 0.45 μm, and the finely ground slurry is subjected to a first spray drying in a spray dryer with an inlet air temperature of 200° C.;

[0070] (3) The spray material obtained in step (2) is sintered at 700° C. for 9 h under an inert atmosphere, and then crushed to obtain a precursor after sintering;

[0071] (4) weighing the precursor, sucrose, polyacrylamide dispersant and deionized water in step (3), adding them to a premixer and premixing for 50 minutes to obtain slurry B, wherein the solid content of slurry B is 60%, the mass of the carbon source is 4% of the mass of the precursor, and the amount of polyacrylamide added is 3% of the mass of the precursor; after completion, transferring to a fine grinder and finely grinding to a D50 of 0.45 μm, and the finely ground slurry is subjected to a second spray drying in a spray dryer with an inlet air temperature of 200° C.;

[0072] (5) The spray material obtained in step (4) is sintered at 400° C. for 2 h under an inert atmosphere, and then crushed to obtain a finished product of lithium iron phosphate.

[0073] Example 3

[0074] The method for preparing lithium iron phosphate provided in this embodiment comprises the following steps:

[0075] (1) Weighing iron phosphate, lithium carbonate, titanium dioxide, lithium dihydrogen phosphate and deionized water, adding them to a sand mill and coarsely grinding them for 20 minutes to obtain slurry A, wherein the solid content of slurry A is 45%, the molar ratio of lithium element, iron element and phosphorus element in slurry A is 1:0.95:0.95, and the concentration of additives in slurry A is 2500 ppm;

[0076] (2) adding sodium dodecyl sulfate dispersant to slurry A in an amount of 60% of the total mass of the iron source and the lithium source, and continuing sand milling for 60 min; after completion, transferring to a fine grinder for fine grinding until D50 is 0.4 μm, and performing a first spray drying in a spray dryer with an air inlet temperature of 200° C.;

[0077] (3) The spray material obtained in step (2) is sintered at 600° C. for 7 h under an inert atmosphere, and then crushed to obtain a precursor after sintering;

[0078] (4) weighing the precursor, sucrose, sodium dodecyl sulfate dispersant and deionized water in step (3), adding them to a premixer and premixing for 50 minutes to obtain slurry B, wherein the solid content of slurry B is 55%, the mass of the carbon source is 2% of the mass of the precursor, and the amount of sodium dodecyl sulfate added is 1% of the mass of the precursor; after completion, transferring to a fine grinder for fine grinding until D50 is 0.4 μm, and the finely ground slurry is subjected to a second spray drying in a spray dryer with an inlet air temperature of 200° C.;

[0079] (5) The spray material obtained in step (4) is sintered at 350° C. for 1 h under an inert atmosphere, and then crushed to obtain a finished product of lithium iron phosphate.

[0080] Example 4

[0081] The method for preparing lithium iron phosphate provided in this embodiment comprises the following steps:

[0082] (1) Weighing iron phosphate, lithium carbonate, titanium dioxide, lithium dihydrogen phosphate and deionized water, adding them to a sand mill and coarsely grinding them for 20 minutes to obtain slurry A, wherein the solid content of slurry A is 55%, the molar ratio of lithium element, iron element and phosphorus element in slurry A is 1:1:1.05, and the concentration of additives in slurry A is 3500 ppm;

[0083] (2) adding a fatty acid polyglycol ester dispersant to slurry A, wherein the amount of fatty acid polyglycol ester added is 80% of the total mass of the iron source and the lithium source, and continuing sand milling for 60 min; after completion, transferring the slurry to a fine grinder for fine grinding until the D50 is 0.5 μm, and performing a first spray drying in a spray dryer with an inlet air temperature of 200° C.;

[0084] (3) The spray material obtained in step (2) is sintered at 800° C. for 11 h under an inert atmosphere, and then crushed to obtain a precursor after sintering;

[0085] (4) weighing the precursor, sucrose, fatty acid polyethylene glycol ester dispersant and deionized water in step (3), adding them to a premixer and premixing for 50 minutes to obtain slurry B, wherein the solid content of slurry B is 58%, the mass of the carbon source is 6% of the mass of the precursor, and the amount of fatty acid polyethylene glycol ester added is 5% of the mass of the precursor; after completion, transferring to a fine grinder and finely grinding to a D50 of 0.5 μm, and the finely ground slurry is subjected to a second spray drying in a spray dryer with an inlet air temperature of 200° C.;

[0086] (5) The spray material obtained in step (4) is sintered at 450° C. for 3 h under an inert atmosphere, and then crushed to obtain a finished product of lithium iron phosphate.

[0087] Comparative Example 1

[0088] The only difference between this comparative example and Example 2 is that no dispersant is added in steps (2) and (4).

[0089] Comparative Example 2

[0090] The only difference between this comparative example and Example 2 is that the sintering temperature in step (5) is 700°C.

[0091] Comparative Example 3

[0092] The only difference between this comparative example and Example 2 is that the amount of polyacrylamide added in step (2) is 90% of the total mass of the iron source and the lithium source.

[0093] Comparative Example 4

[0094] The only difference between this comparative example and Example 2 is that the amount of polyacrylamide added in step (4) is 10% of the mass of the precursor.

[0095] Experimental Example 1

[0096] The solid content of the slurry after fine grinding in steps (2) and (4) of each embodiment and comparative example was tested, and the results are shown in Table 1.

[0097] Table 1

[0098]

[0099] It can be seen from Table 1 that after adding the dispersant, the slurry viscosity is reduced, thereby effectively increasing the slurry solid content.

[0100] Experimental Example 2

[0101] The performance of the lithium iron phosphate prepared in each embodiment and comparative example was tested, and the test results are shown in Table 2.

[0102] Tap density test method:

[0103] 1. Weighing

[0104] Clean the inner wall of the measuring cylinder with a brush, weigh the empty measuring cylinder m1, weigh the sample (10.00g±0.05g) accurate to 0.002g, and put it into the measuring cylinder.

[0105] 2. Sample loading

[0106] Place the measuring cylinder with the weighed sample into the positioning slot of the vibrator density meter. After fixing the measuring cylinder, align the white indentation on the fixture with the black dot on the vibrator.

[0107] 3 Turn on the instrument

[0108] Click the buttons on the screen to set the frequency and number of times. After setting, press the start button. After the test, read the volume of the measuring cylinder (readings at 3 scale positions in a circle), calculate the average volume and record V; at the same time, weigh m2.

[0109] 4. Calculation of results

[0110]

[0111] Compaction density test method:

[0112] 1. Instrument calibration.

[0113] (1) Parameter settings

[0114] First, turn on the instrument power, select the test item in the operation interface on the upper part of the instrument, general material, and set the parameters. Pressure 3T, constant pressure time 30S, mold diameter 13.02mm, mass 1.0000g.

[0115] (2) Place the mold

[0116] Place the molds into the circular holes in order. Open the instrument test window, place the sample table into the base slot, and close the test window.

[0117] (3) Click the instrument zero button and repeat the zeroing process twice.

[0118] 2. Sample measurement;

[0119] (1) Sample pouring

[0120] After zeroing, take out the mold; weigh about 1.0000g of the sample and put it into the mold.

[0121] (2) Take measurements

[0122] Place the mold into the sample slot and input the sample mass (the final mass needs to be tared). Close the test window and click the start button to start the test. After the test stops, read and record the compaction density result with a 3% error.

[0123] (3) Sample demoulding

[0124] After the test is completed, open the test window, take out the mold, replace the demoulding base, put it into the mold slot, close the test window, click the demoulding button on the screen to demould. After the test is completed, take out the mold and clean it.

[0125] Battery low temperature performance test method:

[0126] 1. Temperature control: Before testing, the battery should be left at room temperature for more than 30 minutes, and then placed in a low temperature box with the temperature set at -10℃, -20℃, -30℃, etc.

[0127] 2. Discharge current: The choice of discharge current should take into account the battery model and capacity. Generally, the discharge current should be set at about 0.5 times the rated capacity of the battery.

[0128] 3. Discharge termination voltage: The discharge termination voltage is generally set at about 70% of the rated voltage of the battery.

[0129] Table 2

[0130]

[0131]

[0132] From Table 2, we can see that:

[0133] (1) After using dispersants to replace traditional carbon sources, the tap density and compaction density of the finished lithium iron phosphate are effectively improved.

[0134] (2) Secondary carbon coating can reduce the internal resistance of the material and further improve the conductivity of the lithium iron phosphate material.

[0135] (3) Carbon coating at low temperature can effectively reduce the performance degradation of the battery in low temperature environment. The presence of the carbon layer can reduce the viscosity of the electrolyte and promote the migration of lithium ions, thereby improving the discharge efficiency and capacity of lithium iron phosphate materials at low temperatures.

[0136] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing lithium iron phosphate, characterized in that: The following steps are involved: (a) subjecting a mixed system containing slurry A and a dispersant to first grinding, first spray drying, first sintering and pulverizing to obtain a precursor; The slurry A comprises: an iron source, a lithium source and an additive; (b) subjecting the mixed system containing the precursor, the carbon source and the dispersant to second grinding, second spray drying and second sintering.

2. The method for preparing lithium iron phosphate according to claim 1, characterized in that: Step (a), the mass of the dispersant is 60% to 80% of the total mass of the iron source and the lithium source; And / or, in step (b), the mass of the dispersant is 1% to 5% of the mass of the precursor.

3. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The dispersant includes at least one of polyacrylate, polyacrylamide, sodium lauryl sulfate or fatty acid polyethylene glycol ester.

4. The method for preparing lithium iron phosphate according to claim 1, characterized in that: D of mixed material 50 When the particle size is 0.4 to 0.5 μm, the first polishing and the second polishing are completed.

5. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The first sintering temperature is 600-800°C; And / or, the first sintering time is 7 to 11 hours.

6. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The second sintering temperature is 350-450°C; And / or, the second sintering time is 1 to 3 hours.

7. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The additive comprises: at least one of lithium dihydrogen phosphate, ammonium vanadate, ammonium dihydrogen phosphate, niobium pentoxide or titanium dioxide; And / or, the concentration of the additive is 2500-3500 ppm.

8. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The molar ratio of lithium element, iron element and phosphorus element in the slurry A is 1:0.95 to 1:0.95 to 1.05; And / or, the mass of the carbon source is 2% to 6% of the mass of the precursor.

9. A positive electrode sheet, characterized in that: The invention relates to lithium iron phosphate prepared by the method for preparing lithium iron phosphate according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.